1994
DOI: 10.1080/09084282.1994.9645331
|View full text |Cite
|
Sign up to set email alerts
|

Sources of stress in family members following head or spinal cord injury

Abstract: Sources of stress and perceptions of patients' psychosocial adjustment were comparatively examined in the family members of patients who had sustained moderate to severe closed head injury (CHI) or spinal cord injury (SCI). The family members of the patients with CHI reported significantly greater stress in relation to lack of social support, overcommitment, and difficult personality characteristics of the patient. Physical incapacitation of the patient was the principal source of stress that significantly dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…These consequences often impact upon an individual's community participation and financial independence (Schonherr, Groothoff, Mulder, & Eisma, 2005), relationships (Boschen, Tonack, & Gargaro, 2005;Chan, 2000a), and psychological well-being (Craig, Tran, & Middleton, 2009;Gill, 1999;Vocaturo, 2009). Research has outlined the challenges experienced by families after SCI, including stress, anxiety and depression for the injured individual (Dryden et al, 2005;Hoffman, Bombardier, Graves, Kalpakjian, & Krause, 2011;Kennedy & Rogers, 2000;Williams & Murray, 2015), and distress and burden for family members (Alfano, Neilson, & Fink, 1994;Boschen et al, 2005;Chan, 2000b). However, awareness of the strength and positivity that some individuals with SCI and their family members draw upon is growing (Kennedy, Lude, Elfstrom, & Cox, 2013;Middleton et al, 2014;Simpson & Jones, 2013).…”
Section: Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…These consequences often impact upon an individual's community participation and financial independence (Schonherr, Groothoff, Mulder, & Eisma, 2005), relationships (Boschen, Tonack, & Gargaro, 2005;Chan, 2000a), and psychological well-being (Craig, Tran, & Middleton, 2009;Gill, 1999;Vocaturo, 2009). Research has outlined the challenges experienced by families after SCI, including stress, anxiety and depression for the injured individual (Dryden et al, 2005;Hoffman, Bombardier, Graves, Kalpakjian, & Krause, 2011;Kennedy & Rogers, 2000;Williams & Murray, 2015), and distress and burden for family members (Alfano, Neilson, & Fink, 1994;Boschen et al, 2005;Chan, 2000b). However, awareness of the strength and positivity that some individuals with SCI and their family members draw upon is growing (Kennedy, Lude, Elfstrom, & Cox, 2013;Middleton et al, 2014;Simpson & Jones, 2013).…”
Section: Impactmentioning
confidence: 99%
“…Historically, the challenges experienced by families after SCI, including stress, anxiety, and depression for the injured individual (Dryden et al, 2005; Hoffman, Bombardier, Graves, Kalpakjian, & Krause, 2011; Kennedy & Rogers, 2000; Williams & Murray, 2015), and distress and burden for family members (Alfano, Neilson, & Fink, 1994; Boschen et al, 2005; Chan, 2000b) have been extensively reported. However, these negative impacts are not universal, and more recent research has started to identify how individuals with SCI and their families have coped and adjusted well (Angel, Kirkevold, & Pedersen, 2009; Dickson et al, 2012; Kennedy, Lude, Elfström, & Cox, 2013; Weitzner et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…82 It has been reported that it is not only the perception of physical disability and distress in the patient that creates emotional diculties for their families but it is wider ranging factors such as severe ®nancial hardship or the prospect of ®nancial diculties which are likely to occur as employment is adversely aected. 83 Other studies have reported that the eect of injury on the patient's spouse has been to create a sense of vulnerability in them in terms of the security of the marital relationship. Spouses have reported that they have a stronger fear of separation and a higher sense of dependency as a result of the injury.…”
Section: Eects On the Familymentioning
confidence: 99%
“…The present research is original in its focus on the "lived experience" of being a spousal caregiver and is novel in its use of Interpretative Phenomenological Analysis (IPA) to do so. In contrast to much of the quantitative spinal injury research (Alfano, Neilson & Fink, 1994;Shewchuk et al, 1998;Elliott, Shewchuk & Richards, 2001;Unalan et al, 2001;Meade, Taylor, Kreutzer et al, 2004;Chandler, Kennedy & Sandhu, 2007;Dreer, Elliott, Shewchuk, 2007), the phenomenological focus of this article addresses a hermeneutic of empathy: it seeks to explore the links between what people say and the way in which they think about their own experiences. It's idiographic focus allows for the participant and their experiences to be the unit of analysis as opposed to the discourse or narrative.…”
Section: Introductionmentioning
confidence: 99%